Ethnic differences in the probability of saving and owning land among elderly in Malaysia. - Haron, Sharifah Azizah; Sharpe, Deanna L.; Masud, Jariah; Abdel-Ghany, Mohamed (Malaysian Consumer and Family Economics Association, 2011)
Data from the 2004 Economic and Financial Aspects of Aging in Malaysia were used to examine factors associated with having savings and land ownership among the Malay, Chinese, and Indian elderly in Malaysia. Those with lower levels of education, income and selfreported health were less likely to have savings. Also, Indians were less likely than Malay or Chinese to have savings. Land ownership was more likely for those with higher income, larger family size, the widowed or separated and females. Indians were more likely than Malay or Chinese own land. Value of land holdings was significantly higher for the Chinese as compared to the Malay and Indians.